Neonatal hypoglycaemia and withdrawal symptoms after exposure in utero to valproate. Issue 2 (1st September 2000) - Ebbesen, Finn; Joergensen, Annemette; Hoseth, Eva; Kaad, Per-Henrik; Moeller, Margrethe; Holsteen, Vibeke; Rix, Mariane
Abstract : AIMS: To define, in a prospective study, the risk of hypoglycaemia—defined as blood glucose concentration < 1.8 mmol/l—in term infants exposed in utero to valproate and to describe the withdrawal symptoms. METHODS: Twenty epileptic women were treated with valproate only during pregnancy and two were treated with valproate and carbamazepine. In the first trimester, the daily median dose of valproate was 1.0 g (range 0.3–4.2) and in the third trimester 1.2 g (range 0.3–4.8). RESULTS: Thirteen of the 22 infants became hypoglycaemic. One infant had eight episodes of hypoglycaemia, one had three episodes, two had two episodes, and nine had one episode each. The lowest blood glucose concentration was 1.0 mmol/l. All episodes were asymptomatic. The maternal mean plasma concentration of total valproate during the third trimester correlated negatively with blood glucose concentration one hour after delivery (p < 0.0003) and with the development of hypoglycaemia (p < 0.0001). There was no evidence for hyperinsulinaemia as the cause of hypoglycaemia. Ten infants developed withdrawal symptoms, which correlated positively with the mean dose of valproate in the third trimester and the concentration of the free fraction of valproate in maternal plasma at delivery (p < 0.02). CONCLUSIONS: Infants exposed to valproate in utero had a significantly elevated risk of hypoglycaemia, and withdrawal symptoms were often observed.